Learning innovation: Reconstruction laboratory activities design on respiratory air and designing a simple spirometer - Solikhah Isti Fadilah; Bambang Supriatno; Alfyn Abdan Nurahman; Amprasto Amprasto (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Laboratory practicum in science learning is considered important, especially in the context of the Independent Curriculum. Science-based learning is needed to encourage the development of students' skills and character, supported by practical activities. Good practical activities not only allow students to understand scientific concepts but also train students to apply scientific methods effectively. The aim of this research is to analyze, reconstruct, and design simple tools to improve Laboratory Activities Designed (LAD) on the respiratory air sub-material. The research method used is descriptive to show existing phenomena. Analysis was carried out using Vee Diagrams; then trials were carried out, reconstruction and design of simple tools, second trials, and revisions. The results of the analysis show that the five LAD samples are still in the very poor category, so improvements need to be made to avoid mistakes in the future. Researchers carried out LAD reconstruction, which included appearance, title, purpose, tools and materials, procedures, and questions. Reconstruction is supported by designing a tool in the form of a simple spirometer. The design of this simple tool can be assigned to students to train creativity and solve problems. It is hoped that the results of this analysis and reconstruction can help teachers in designing LAD for other materials in the future to suit learning objectives and the applicable curriculum.Abstract. Praktikum laboratorium dalam pembelajaran sains dinilai penting terutama dalam konteks Kurikulum Merdeka. Pembelajaran berbasis sains diperlukan untuk mendorong pengembangan keterampilan dan karakter siswa dengan didukung kegiatan praktikum. Kegiatan praktikum yang baik tidak hanya memungkinkan siswa untuk memahami konsep sains, tetapi juga melatih siswa dalam menerapkan metode ilmiah dengan efektif. Tujuan penelitian ini yaitu untuk menganalisis, melakukan rekonstruksi dan merancang alat sederhana untuk menyempurnakan Laboratory Activities Designed (LAD) pada sub materi udara hasil pernafasan. Metode penelitian yang digunakan yaitu deskriptif untuk menunjukkan fenomena yang ada. Analisis dilakukan menggunakan Diagram Vee, selanjutnya dilakukan uji coba, rekonstruksi dan perancangan alat sederhana, uji coba kedua, dan revisi. Hasil analisis menunjukkan bahwa kelima sampel LAD masih dalam kategori sangat buruk sehingga perlu dilakukan perbaikan untuk menghindari kekeliruan di masa yang akan datang. Peneliti melakukan rekonstruksi LAD yang mencakup tampilan, judul, tujuan, alat dan bahan, prosedur, dan pertanyaan. Rekonstruksi didukung dengan perancangan alat berupa spirometer sederhana. Perancangan alat sederhana ini dapat ditugaskan kepada siswa untuk melatih kreativitas dan memecahkan masalah. Hasil analisis dan rekonstruksi ini diharapkan dapat membantu guru-guru dalam merancang LAD materi lain di masa depan agar sesuai dengan tujuan pembelajaran dan kurikulum yang berlaku.